The social impact of artificial intelligence chatbots on college students - Hakimi, Azman; Meng Yue, Reeda Li; Muhsin, Mariam Sufiah; Bakar, Maisarah Abu; Yen Teng, Crendy Tan; Prihadi, Kususanto Ditto (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study aims to investigate the impact of the freely accessible artificial intelligence chatbots (AICB) that might disrupt the teaching and learning pattern in higher education. While some education stakeholders developed strong opposition towards the AICB usage, condemning it as academic dishonesty, there are others believe the AICB might even improve the students’ learning. A total of 160 urban college students were purposively selected and requested to respond to the scales of ChatGPT acceptance and trust, academic self-efficacy, and university mattering to test the hypothesis that the acceptance and trust towards AICB should improve academic self-efficacy and general mattering among the students. The results indicated that academic self-efficacy partially mediates the contribution of AICB on the societal mattering. In other words, the findings suggest that students who trust and accept AICB usage would likely to believe that they can perform academically better and therefore they feel they are more meaningful to the society. Limitations and suggestions for future research are discussed.